Dyslipidemia involvement in the development of polycystic ovary syndrome - Qi Liu; Yuan-jie Xie; Li-hua Qu; Meng-xia Zhang; Zhong-cheng Mo (Elsevier, 2019)
Polycystic ovary syndrome (PCOS) is widely accepted as the most common endocrine abnormality in women of childbearing age and may be accompanied by dyslipidemia, hyperandrogenism, hyperinsulinemia, oxidative stress and infertility. Dyslipidemia is now known to play an important role in the development of PCOS. Lipid abnormalities, including elevated low-density lipoprotein and triglyceride levels and reduced high-density lipoprotein levels, are often found in women with PCOS and play an important role in PCOS; therefore, we summarize the effect of lipid abnormalities on hyperandrogenism, insulin resistance, oxidative stress and infertility in PCOS and review the effects of common lipid-lowering drugs on patients with PCOS. The purpose of this article is to elucidate the mechanisms of lipid metabolism abnormalities in the development of PCOS. Keywords: Polycystic ovary syndrome, Lipid, Hyperandrogenism, Insulin resistance, Lipid-lowering drugs